2020
DOI: 10.1021/acs.jpcc.0c02199
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Interfaces of Janus Monolayers of Transition Metal Dichalcogenides for 2D Photovoltaic and Piezoelectric Applications

Abstract: Using first-principles calculations, we demonstrate a combination of two emergent fields, type II van der Waals heterostructures and Janus structures, for the purpose of optimizing the harvesting of solar and nano-electromechanical energy. The most stable stacking order in these nanoscale heterobilayers comprising Janus monolayers of transition metal dichalcogenides has been ascertained based on the interlayer binding energies. The binding energies in WSeTe/WSTe and MoSeTe/WSTe heterobilayers are found to be −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 92 publications
3
71
1
Order By: Relevance
“…Recently, TMDs with their unique crystal structures, superior properties, and exotic functionalities have drawn intense attention in applications for piezoelectric devices, [ 319–321 ] batteries, [ 322–324 ] electronic devices, [ 325,326 ] photocatalysis, [ 327–331 ] biomedicine, [ 332–334 ] and PEC sensing. [ 335,336 ] In this regard, 2D TMDs can play an important role in energy production in the future.…”
Section: Photoelectrochemical Properties Of Cuo Compositesmentioning
confidence: 99%
“…Recently, TMDs with their unique crystal structures, superior properties, and exotic functionalities have drawn intense attention in applications for piezoelectric devices, [ 319–321 ] batteries, [ 322–324 ] electronic devices, [ 325,326 ] photocatalysis, [ 327–331 ] biomedicine, [ 332–334 ] and PEC sensing. [ 335,336 ] In this regard, 2D TMDs can play an important role in energy production in the future.…”
Section: Photoelectrochemical Properties Of Cuo Compositesmentioning
confidence: 99%
“…since the first discovery of single atomic thickness graphene. Thus, piezotronics based on 2D materials was presented and developed rapidly from microscopic mechanism, various materials to the practical applications on nanogenerators, sensors, catalysis, information storage, and other flexible devices 42–54 …”
Section: Introductionmentioning
confidence: 99%
“…Simulation of both classes of hetero-structures reveals type-II band alignment (staggered gap), where both the VBM and CBM of one component is a little higher than that of the other one, and accordingly favorable separation of excitons. Furthermore, Rawat et al [72] investigated a series of Janus hetero-structures formed by different kinds of Janus TMDs as MoXY/WXY (X, Y=S, Se, Te). They found that, depending on the composition and structure of the Janus TMD, the band gap can be tuned to a large extent from the infrared area to the ultraviolet region.…”
Section: Hetero-structuresmentioning
confidence: 99%
“…They found that, depending on the composition and structure of the Janus TMD, the band gap can be tuned to a large extent from the infrared area to the ultraviolet region. [72] In addition to hetero-structures consisting of two different Janus TMDs, research has also been carried out in other hetero-structures made up of Janus TMDs interfaced with other conventional two-dimensional materials. For instance, we investigated the heterostructure formed by combining Janus MoSSe with nitride semiconductors, namely MoSSe/XN (X=Al, Ga).…”
Section: Hetero-structuresmentioning
confidence: 99%